Is there an optimal management for localized prostate cancer? - Singh, Jaspreet (Dove Medical Press, 2010)
Widespread screening with prostate-specific antigen (PSA) has led to a significant increase in the detection of early stage, clinically localized prostate cancer (CaP). Various treatment options for localized CaP are discussed in this review article including active surveillance, radical prostatectomy, radiation therapy, and cyrotherapy. The paucity of high-level evidence adds a considerable amount of controversy when choosing the “optimal” intervention, for both the treating physician and the patient. The long time course of CaP intervention outcomes, combined with continuing modifications in treatments, further complicate the matter. Lacking randomized trials that compare treatment options, this review article attempts to summarize the different treatment options and associated side-effects, including effects on health-related quality of life, from current published literature.